Intraoperative cell-salvaged versus allogeneic red blood cell transfusions in high-bleeding-risk cardiovascular surgery: Protocol for a single-center, randomized, parallel-group, noninferiority trial - Akito Tsukinaga; Kenji Yoshitani; Soshiro Ogata; Takahiro Mihara; Shin Ito; Hiroko Kanazawa; Akira Shimokawa; Sho Masuda; Masahiro Morinaga; Yoshiaki Ito; Shinnosuke Miura; Naonori Kawamoto; et al. (PLoS ONE, 2025)
Introduction Patients who undergo cardiac surgery have a high risk of significant blood loss and anemia. While allogeneic red blood cell (RBC) transfusions are effective, they are associated with increased morbidity and mortality. Intraoperative cell salvage may reduce reliance on allogeneic transfusions. Although intraoperative RBC salvage is recommended for cardiovascular surgery under cardiopulmonary bypass, there are concerns about increased bleeding due to coagulopathy in patients with a high bleeding risk, and its clinical impact remains unclear. This study aims to evaluate whether salvaged RBC transfusion is noninferior to allogeneic transfusion in terms of postoperative blood loss in patients with a high bleeding risk. Methods This single-center, randomized, two-arm, parallel group, interventional clinical trial will include 142 participants aged ≥ 40 years with a high bleeding risk who undergo elective cardiovascular surgery with cardiopulmonary bypass. Participants will be randomly assigned to receive either salvaged RBC or allogeneic RBC transfusions intraoperatively. The primary outcome is postoperative chest tube blood loss within 12 hours from the end of surgery. Noninferiority will be demonstrated if the upper limit of the 95% confidence interval for the mean difference in blood loss between the salvaged and allogeneic groups is < 200 mL. Secondary outcomes comprise the RBC transfusion volume intraoperatively and for 12 hours from the end of surgery, prevalence of re-thoracotomy within 48 hours from the end of surgery, and prevalence of ≥ 1000 mL postoperative chest tube blood loss within 12 hours from the end of surgery. These outcomes will be analyzed using the modified intention-to-treat set and repeated, for sensitivity reasons, for the per-protocol set. Discussion Our trial aims to determine the noninferiority of intraoperative RBC salvage compared with allogeneic blood transfusions regarding postoperative blood loss and to promote its use in surgical procedures with a high bleeding risk. Trial registration The trial was registered with the Japan Registry of Clinical Trials (jRCT1052240102) on July 30, 2024.